Towards student engagement in listening to the target language beyond classroom - Ta, Thi Thanh Hoa (2018)
It is well-established that student engagement is a prerequisite and proxy for learning and development. Yet, despite its significance, student engagement has not received proper attention as an important construct in the literature of second/foreign language research, especially in research on listening skill. The current research contributes to the understanding of the phenomenon of student engagement in out-of-class L2 listening. The research was conducted at a university in Viet Nam and targeted at second-year and third-year majors of English as a Foreign Language (EFL). To attain the aims of gaining insight into student engagement in listening beyond classroom and innovating a design for enhancing student engagement, two studies were undertaken. The first or baseline study examined the status quo of student engagement within these learners’ usual self-study setting. Meanwhile, the main study examined student engagement in the project’s social networked or YouListen listening space. The research was a mixed methods case study, mobilizing survey questionnaires, a record of the learners’ online activity and semi-structured interviews. The results from the baseline study reveal a worrying status quo of student engagement in terms of time and effort investment, listening strategy use, readiness, confidence and willingness to listen to the target language beyond classroom. Besides, the learning condition and factors relating to the learners themselves were perceived to affect their engagement the most. Furthermore, several significant correlations between certain behaviours of engagement were statistically identified. Last, sharing experiences with peers, asynchronous communication, test-oriented resources and real life-oriented resources gained the learner’s strong favour. The findings of the main study depict a diverse picture of student engagement in which variation in engagement was associated with different learners and different listening or sharing sub-spaces and within individual learners. In general, there were noticeable positive signs of engagement, such as being engaged with particular listening resources, the expression of positive emotions, and actively sharing listening comprehension and reflection, all of which seemed to suggest the potential of the project’s listening space to engage learners to listen actively to English. Nevertheless, the prevalence of inflexible listening strategies and ‘quiet’ knowledge construction were identified. It was found that there was interplay of certain contextual and learner factors that might have contributed to the ways students engaged. Suggestions that might further promote student engagement were drawn and involved improvements in both the design and the learner. Based on the obtained research findings, pedagogical implications are recommended. The findings and recommendations will be of interest to EFL teachers, researchers, and policy makers.